Penerapan Community Based Tourism untuk Meningkatkan Wisatawan dalam Pengembangan Wisata Kota Lama Surabaya - Nabila, Balqis; Kendry Widiyanto, M.; Ismail, Hasan (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
Surabaya Old Town has significant potential as a heritage tourism destination that can support local economic growth and cultural preservation. This study analyzes the application of Community-Based Tourism (CBT) in the area, focusing on five dimensions proposed by Suansri (2003) economic, social, cultural, environmental, and political. Using a descriptive qualitative approach, data was collected through interviews, observations, and document studies. The results show that despite revitalization efforts, community involvement in tourism development remains limited. Key challenges include insufficient training, inadequate infrastructure, and limited coordination among stakeholders. Nevertheless, more than 50 SMEs and informal job opportunities have emerged, although sustaining this economic growth remains a challenge. This study emphasizes the importance of community capacity building and the establishment of community forums as policy partners. Recommendations include cross-sector collaboration to make Surabaya Old Town an inclusive and sustainable heritage tourism destination.